A photoprogrammable electronic nose with switchable selectivity for VOCs using MOF films. Issue 47 (22nd November 2021) - Qin, Peng; Okur, Salih; Li, Chun; Chandresh, Abhinav; Mutruc, Dragos; Hecht, Stefan; Heinke, Lars
Abstract : A sensor array with four identical photoresponsive azobenzene-containing metal–organic framework films is selectively irradiated. By photoprogamming the array, the sensor selectivity is switched and optimized. Abstract : Advanced analytical applications require smart materials and sensor systems that are able to adapt or be configured to specific tasks. Based on reversible photochemistry in nanoporous materials, we present a sensor array with a selectivity that is reversibly controlled by light irradiation. The active material of the sensor array, or electronic nose (e-nose), is based on metal–organic frameworks (MOFs) with photoresponsive fluorinated azobenzene groups that can be optically switched between their trans and cis state. By irradiation with light of different wavelengths, the trans – cis ratio can be modulated. Here we use four trans – cis values as defined states and employ a four-channel quartz-crystal microbalance for gravimetrically monitoring the molecular uptake by the MOF films. We apply the photoprogrammable e-nose to the sensing of different volatile organic compounds (VOCs) and analyze the sensor array data with simple machine-learning algorithms. When the sensor array is in a state with all sensors either in the same trans - or cis -rich state, cross-sensitivity between the analytes occurs and the classification accuracy is not ideal. Remarkably, the VOC molecules between which the sensor array shows cross-sensitivity vary by switching the entire sensor array from trans to cis . By selectively programming the e-nose with light of different colors, each sensor exhibits a different isomer ratio and thus a different VOC affinity, based on the polarity difference between the trans - and cis -azobenzenes. In such photoprogrammed state, the cross-sensitivity is reduced and the selectivity is enhanced, so that the e-nose can perfectly identify the tested VOCs. This work demonstrates for the first time the potential of photoswitchable and thus optically configurable materials as active sensing material in an e-nose for intelligent molecular sensing. The concept is not limited to QCM-based azobenzene-MOF sensors and can also be applied to diverse sensing materials and photoswitches.